Renewable Energy and Green Technology : Principles and Practices - Kumar, Narendra; Singh, Hukum; Kumar, Amit (Boca Raton: CRC Press, 2022)
Renewable Energy and Green Technology: Principles and Practices is based on the present need to understand the principles and utility of renewable energy and green technology to minimize dependency on fossil fuels in global development. Renewable energy is the best and cheapest source of energy as an alternate resource. There is massive potential for renewable energy globally, including in India. The efficient utilization of renewable energy resources could minimize the impact of climate change globally. Generally, renewable energy is generated from essentially inexhaustible sources, including wind power, solar power, geothermal energy, tidal energy, biomass energy, and other sources. Hence, encouraging renewable energy use could save our tomorrow from the climate change perspective and in terms of sustainable food production. This book promotes the exchange of ideas, policy formulation, and collective action to ensure a smooth transition to renewable energy. It describes the technological interventions for reducing environmental and economic damage resulting from the use of conventional energy sources. In this book, the focus is on utilizing various renewable energy sources in diverse sectors. It also elaborates the descriptive methodology of different renewable energies, accompanied by figures and tables. It provides information on biogas energy plants, gasifier technologies, and hydropower technologies, among others, along with their applications. Further, it delves into energy concepts and details significant advantages of the energy resources for sustaining the future world. Lastly, this book will provide instant access to comprehensive, cutting-edge knowledge, making it possible for academicians and researchers to utilize this ever-growing wealth of information.
Keywords: Renewable energy sources; Green technology; Environmental protection$1 (BTechnological innovationss; Sustainable development